Adapting to Change: A Theoretical Framework for Agile HR in Recruiting - Diana Ivana (Romanian Economic Journal)
The COVID-19 pandemic changed the IT industry and made agile HR procedures necessary to meet changing corporate objectives and fluctuating staffing demands. Agile HR, which draws inspiration from Agile approaches in software development, places a strong emphasis on adaptability, teamwork, and reactivity in order to improve organizational resilience and employee engagement. In order to fill the gap in the literature on Agile HR, this article offers a conceptual framework for putting Agile HR methods into practice, with an emphasis on hiring in the IT&C sector. Iterative, data-driven, and collaborative approaches to talent acquisition are highlighted in the study using qualitative data from three IT businesses. As a framework to help businesses navigate today's dynamic business climate, the findings show how Agile HR improves organizational performance, productivity, and adaptability.